2008
DOI: 10.1016/j.cogsys.2007.07.002
|View full text |Cite
|
Sign up to set email alerts
|

A conceptual and empirical framework for the social distribution of cognition: The case of memory

Abstract: In this paper, we aim to show that the framework of embedded, distributed, or extended cognition offers new perspectives on social cognition by applying it to one specific domain: the psychology of memory. In making our case, first we specify some key social dimensions of cognitive distribution and some basic distinctions between memory cases, and then describe stronger and weaker versions of distributed remembering in the general distributed cognition framework. Next, we examine studies of social influences o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
144
0
9

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(156 citation statements)
references
References 81 publications
(92 reference statements)
3
144
0
9
Order By: Relevance
“…The social nature of encoding can be conceptualized as existing on a continuum, ranging from completely unshared to completely shared (see also Barnier et al, 2008). On this continuum, our shared encoding task ranked relatively highly, since it was an interactive task that required discussion between group members and involved linking each word to the groups' existing shared knowledge and an agreed-upon cue.…”
Section: Discussionmentioning
confidence: 99%
“…The social nature of encoding can be conceptualized as existing on a continuum, ranging from completely unshared to completely shared (see also Barnier et al, 2008). On this continuum, our shared encoding task ranked relatively highly, since it was an interactive task that required discussion between group members and involved linking each word to the groups' existing shared knowledge and an agreed-upon cue.…”
Section: Discussionmentioning
confidence: 99%
“…After the instructional sequences everyone cuts Brussels sprouts for a while and everyone's attention and gaze is directed at the work process on the Anette comments that they are working like an assembly line (19)(20)(21)(22).…”
Section: Chopping Brussels Sprouts: Shared Attentionmentioning
confidence: 99%
“…Developmental psychologists have suggested that collaboration between children as well as with grown-ups are essential for understanding psychological development (Lave & Wenger, 1991;Rogoff, 1998). Other researchers have pointed out that many cognitive tasks as well as the performance of many everyday chores presuppose collaboration between several persons and that they share cognitive resources in the collaborative process (Barnier, Sutton, Harris & Wilson, 2008;Clark, 1996;Hutchins, 1996;Michaelian & Sutton, 2013;Sawyer, 2003). Finally a number of researchers have shown how persons with cognitive and communicative disabilities can communicate and solve problems through collaboration with others and compensate cognitive loss by drawing on the cognitive and linguistic resources of other participants (Dixon & Gould, 1998;Goodwin, 2004;Harris, Keil, Sutton, Barnier & McIlwain, 2011;Müller & Mok, 2013).…”
mentioning
confidence: 99%
“…11 Proponents of the distributed cognition thesis go even further: they claim that a cognitive system could extend to include not only an artifact which an individual agent uses, but also several individuals and their epistemic artifacts (Hutchins, 1995, Theiner & O'Connor, 2010, Sutton et al, 2008. In other words, a cognitive process could be distributed among several individuals and their epistemic artifacts.…”
Section: The Process-centered Approach Of Group Knowledgementioning
confidence: 99%
“…For the discussion on the extended mind and the extended cognition theses see: (Trybulec, 2014a(Trybulec, , 2014b(Trybulec, , 2015b. the existence of non-linear relations that arise out of continuous reciprocal interactions between the contributing parts (Palermos, 2015;Chemero, 2009;Sutton et al, 2008;Theiner & O'Connor, 2010;Wegner et al, 1985). These relations give rise to new properties of a system that do not belong to its individual parts.…”
Section: The Process-centered Approach Of Group Knowledgementioning
confidence: 99%